Rekognisi Hukum Pidana Adat di Era Modernisasi Hukum Nasional - Badrut Tamam; Yudha Bagus Tunggala Putra (Policy and Law Journal, 2025)
This study aims to analyze the integration of customary criminal law into the national legal system based on the principles of justice and the values of Pancasila. The research adopts a normative legal method by analyzing statutory regulations, legal concepts, and relevant cases. It also explores the philosophical foundations and the ratio legis of recognizing customary criminal law within the context of legal modernization, as reflected in the new Criminal Code under Law Number 1 of 2023. The findings indicate that customary criminal law holds a significant position as a reflection of social justice in local communities. However, its integration into the national legal system faces challenges, particularly in harmonizing customary law principles with modern legal norms. This study concludes that the principles of justice enshrined in Pancasila can serve as an ethical framework to align customary criminal law with national law, fostering an inclusive and culturally responsive legal system in Indonesia.